Integrating expressive arts and play therapy with children and adolescents (Wiley, 2014)
"Clinicians certified in the expressive art therapies--the visual arts, movement, drama, music, writing and other creative processes--are typically unfamiliar with some of the interventions and approaches used in play therapy. This book bridges the divide between play therapy and expressive arts therapy, so that therapists in each field can integrate evidence-informed practices from both expressive arts and play therapy into their practice with children and adolescents. Play therapists as well as those who specialize in expressive arts therapies, as well as mental health professionals looking to integrate both into their practice will benefit from this book's exposure to the diverse and innovative approaches within the expressive arts and play therapy literature"--Provided by publisher.